PERFUSION DYSFUNCTION IN ACUTE PANCREATITIS: PERSPECTIVES IN IMPROVING DIAGNOSIS AND STRATIFICATION - N.R. Kerbazh; S.I. Panasenko (Проблеми екології та медицини)
Introduction. Acute pancreatitis (AP) is one of the most common diseases of the digestive system that require hospitalization. To date, the problem of stratification and differential diagnosis of AP in the early stages remains unresolved, which encourages the search for new methods of diagnosis and prediction of the severity of AP. Aim. To evaluate the possibility of creating a clinically oriented system of stratification and prognosis of AP on the basis of dynamic changes in microcirculation depending on the duration of the disease and severity of AP. Materials and methods. Assessment of the state of microcirculation (MC) of patients by laser Doppler flowmetry (LDF) was performed with the “LAKK-02” device. Kruskal-Wallis non-parametric analysis of variance and the median test were used to test statistical hypotheses when comparing independent samples. Pairwise comparison of independent samples was performed using the Mann-Whitney U test. Results. The study determined the indicators of MC in patients with different AP severity degrees on the first day of the disease. The microcirculation parameter (MP) in patients with mild, moderate, and severe AP was 3.9; 3.8 and 6.8 perfusion units (p.u.), respectively. The blood flow modulation rate (ơ) was 0.52; 0.54 and 0.69 p.u. in mild, moderate, and severe AP. In our study, the coefficient of variation (Kv) averaged 17.3%; 20.0% and 11.7% in patients with mild, moderate, and severe AP, respectively. Conclusions. LDF in AP is an informative method of diagnosing the state of MC, which is a universal link in all pathophysiological reactions of the organism. Changes of MC in AP depend on the severity of AP and the period of the disease. The pathophysiological microcirculatory phenomena, revealed on the first day of the disease, provide us with the perspectives of early clinical distinguishing the moderate and severe forms of AP from the so-called group of “destructive forms”.